E-COMMERCE APPLICATION UI/UX DESIGNAS A PROMOTIONAL SOLUTIONPOST-PANDEMI SOLO BATIK FABRIC - Nur Cahyo, Dwi
The development of information and communication technology has had a significant impact on various aspects of life, including trade. One form of trade that is increasingly developing is electronic commerce or e-commerce. E-commerce makes it easy for users to make buying and selling transactions online, without having to meet physically face to face. During the COVID-19 pandemic, ecommerce has become the main solution for maintaining business continuity by minimizing physical contact between sellers and buyers. In Indonesia, one of the leading products in the field of trade is Solo batik cloth. Solo batik cloth has a wealth of motifs and artistic beauty that is highly appreciated, both at home and abroad. However, the COVID-19 pandemic has had quite a significant impact on the Solo batik cloth industry, especially in terms of promotion and sales. Limited physical interaction and movement restrictions have hampered efforts to promote and sell conventional Solo batik cloth. In this context, designing a good user interface and user experience in the e-commerce application of Solo batik cloth is very important. A good UI/UX will provide a pleasant shopping experience and make it easier for users to explore, select, and buy Solo batik fabrics. Therefore, this study aims to design the UI/UX of e-commerce applications as a post-pandemic solution for promoting Solo batik cloth.